Predictors of micronutrient status among six- to twelve-month-old breast-fed Ghanaian infants - Lartey, A.; Manu, A.; Brown, K.H.; Dewey, K.G. (Journal of Nutrition, 2000)
This study describes the factors associated with hemoglobin and plasma ferritin, zinc and retinol concentrations and erythrocyte riboflavin status among 208 Ghanaian infants who participated in a complementary feeding intervention trial from 6 to 12 mo of age. Anthropometric, morbidity and dietary data were collected regularly from 1 to 12 mo; blood samples were collected at 6 and 12 mo. The prevalence of low micronutrient status at 6 and 12 mo, respectively, was as follows: hemoglobin <100 g/L, 30 and 34%; plasma ferritin <12 μg/L, 17 and 43%; plasma zinc <10.7 μmol/L, 4 and 6%; plasma retinol < 0.7 μmol/L, 26 and 26%; erythrocyte riboflavin <200 μmol/L of packed red cells, 14 and 10%. Multiple regression was used to identify factors significantly associated with micronutrient status. From 6 to 12 mo, fever prevalence was associated with a decrease in hemoglobin, but an increase in erythrocyte riboflavin concentrations, and diarrhea prevalence was related to a decrease in plasma retinol. Seasonal differences were evident for most of the indicators of micronutrient status, and elevated C- reactive protein levels (indicative of recent infection) were related to lower hemoglobin, retinol and zinc concentrations but higher ferritin and erythrocyte riboflavin concentrations. Weight at birth or at 1 mo of age was positively related to iron, zinc and vitamin A status, but a more rapid weight gain was associated with depletion of iron stores. Socioeconomic status was related to higher hemoglobin, riboflavin and zinc concentrations. The feeding of a micronutrient-fortified food was positively associated with plasma ferritin and retinol concentrations at 12 mo. These results suggest that prenatal factors, socioeconomic status, dietary intake and morbidity all influence infant micronutrient status, and that fortification of complementary foods is one potential avenue for preventing deficiencies.
Keywords: Anemia; Ferritin; Humans; Riboflavin; Vitamin A; Zinc